Phase I study on the pharmacokinetics of intravaginal, self-administered artesunate vaginal pessaries among women in Kenya - Chemtai Mungo; Katherine Sorgi; Brenda Misiko; Cynthia Cheserem; Lisa Rahangdale; George Githongo; Cirilus Ogollah; Jackton Omoto; Mihaela Plesa; William Zamboni (PLoS ONE, 2025)
Cervical cancer remains a significant global health issue, especially in low- and middle-income countries (LMICs), where access to prevention and treatment is limited and women are at a higher risk of cervical cancer. Artesunate, a widely available drug used to treat malaria, has shown promise in treating human papillomavirus (HPV)-associated anogenital lesions including high-grade cervical precancer, in a recent Phase I studies in the United States. Data on the pharmacokinetics of artesunate following intravaginal use, and its implications on malaria resistance, are lacking. Objectives The primary objective of this study is to investigate the pharmacokinetics of Artesunate (AS) and its active metabolite, dihydroartemisinin (DHA) following intravaginal use at the dosing and frequency intended for cervical precancer treatment. A secondary objective is to assess safety among study participants. Methods We are conducting a single-arm, phase I trial with a sample size of 12 female volunteers. Participants will self-administer artesunate vaginal pessaries in the study clinic daily for 5 consecutive days. Participants will have their blood drawn prior to receiving the first dose of artesunate on day one of the study and then will receive 8 blood draws on study day five, prior to artesunate administration and at 15 minutes, 30 minutes, 1 hour, 2 hours, 4 hours, 6 hours, and 8 hours after pessary administration. Pharmacokinetic parameters of artesunate and DHA will be calculated by way of quantitative analysis of with determination of maximum concentration (Cmax), time to Cmax (Tmax), area under the serum concentration versus time curve (AUC), apparent clearance, and elimination half-life (t1/2).